CD226 Deletion Reduces Type 1 Diabetes in the NOD Mouse by Impairing Thymocyte Development and Peripheral T Cell Activation - Shapiro, Melanie R.; Yeh, Wen-I; Longfield, Joshua R.; Gallagher, John; Infante, Caridad M.; Wellford, Sarah; Posgai, Amanda L.; Atkinson, Mark A.; Campbell-Thompson, Martha; Lieberman, Scott M.; Serreze, David V.; Geurts, Aron M.; et al. (Frontiers in Immunology, 2020)
The costimulatory molecule CD226 is highly expressed on effector/memory T cells and NK cells. Costimulatory signals received by T cells can impact both central and peripheral tolerance mechanisms. Genetic polymorphisms in CD226 have been associated with susceptibility to type 1 diabetes and other autoimmune diseases. We hypothesized that genetic deletion of Cd226 in the non-obese diabetic (NOD) mouse would impact type 1 diabetes incidence by altering T cell activation. CD226 knockout (KO) NOD mice displayed decreased disease incidence and insulitis in comparison to wild-type (WT) controls. Although female CD226 KO mice had similar levels of sialoadenitis as WT controls, male CD226 KO mice showed protection from dacryoadenitis. Moreover, CD226 KO T cells were less capable of adoptively transferring disease compared to WT NOD T cells. Of note, CD226 KO mice demonstrated increased CD8+ single positive (SP) thymocytes, leading to increased numbers of CD8+ T cells in the spleen. Decreased percentages of memory CD8+CD44+CD62L- T cells were observed in the pancreatic lymph nodes of CD226 KO mice. Intriguingly, CD8+ T cells in CD226 KO mice showed decreased islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP)-tetramer and CD5 staining, suggesting reduced T cell receptor affinity for this immunodominant antigen. These data support an important role for CD226 in type 1 diabetes development by modulating thymic T cell selection as well as impacting peripheral memory/effector CD8+ T cell activation and function.